Always on the Receiving End? Reflections on Archaeology, Museums and Policy. (3rd July 2019) - Boyle, Gail
ABSTRACT: The Society for Museum Archaeology (SMA) is a Subject Specialist Network for British Archaeology in the UK. Founded in 1975, it was originally formed because of a perceived need for a political voice at a time of evolutionary change in the role for museums relative to the archaeological profession. Since then the role of museum archaeologists has been transformed by policies and other agendas not of their own making. As a consequence, the profession faces multiple challenges requiring new strategies to be formulated and there have been fundamental changes in the way that museums participate in a more professionalised yet compartmentalised fieldwork process. In particular museums have had to deal with the results of changing attitudes towards the preservation and recording of archaeological sites and the introduction of new planning policy. As a result, new standards have evolved, professional groupings formed and resources stretched to breaking point. SMA has been working collaboratively towards finding solutions to the shared challenges the profession faces as a result of policy. Observations on the response to some of these challenges are illustrated here using SMA's newsletters and other publications and commentary provided on recent approaches that have been taken to resolving them.